Can 'democratic management' improve labour relations in market‐driven China?. (15th January 2016) - Huang, Wei; Li, Yuhui; Wang, Shuo; Weng, Jingjing
Abstract : Democratic management is a notion of worker democracy unique to China. It has been revived and extended legislatively to enterprises of all types in the past decade. Can democratic management bring about mutually beneficial labour relations in China? Drawing on social exchange theory, this study uses mixed methods to explore employees' current experience and the outcomes of democratic management in Chinese coal‐mining firms. An employee survey reports a positive relationship between employees' perceived efficacy of democratic management and wider organizational commitment. It suggests that democratic management has the potential value of creating a harmonious labour relationship. However, the success of such management is subject primarily to the commitment of top managers. The triality of motives for top management to conduct democratic management may undermine employees' organizational commitment when employees perceive that top managers are more committed to an exchange relationship with the higher authorities than one with employees. Key points: Democratic management has the potential to bring about mutually beneficial labour relations in Chinese companies. To build a harmonious labour relationship, democratic management should focus on the exchange relationship between the organization and the workers. To increase employee satisfaction with HR practices and their commitment, companies should incorporate democratic management into their organizational decision‐making processes rather than treating it as a 'rubber stamp'.